2016
DOI: 10.1158/0008-5472.can-16-1099
|View full text |Cite
|
Sign up to set email alerts
|

GON4L Drives Cancer Growth through a YY1–Androgen Receptor–CD24 Axis

Abstract: In principle, the inhibition of candidate gain-of-function genes defined through genomic analyses of large patient cohorts offers an attractive therapeutic strategy. In this study, we focused on changes in expression of CD24, a well validated clinical biomarker of poor prognosis and a driver of tumor growth and metastasis, as a benchmark to assess functional relevance. Through this approach, we identified GON4L as a regulator of CD24 from screening a pooled shRNA library of 176 candidate gain-of-function genes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…CD24 is a glycosylphosphatidylinositol-anchored membrane protein reported to be overexpressed in many tumor types, including colorectal cancer, 13 ovarian cancer, 7 bladder cancer, 14 prostate cancer, 5,11 lung cancer, 12 and breast cancer. 9 CD24 plays important roles in tumorigenesis, [35][36][37] progression [38][39][40] and drug resistance. 18,41 CD24 is considered to be a negative cancer stem cell marker, specifically in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CD24 is a glycosylphosphatidylinositol-anchored membrane protein reported to be overexpressed in many tumor types, including colorectal cancer, 13 ovarian cancer, 7 bladder cancer, 14 prostate cancer, 5,11 lung cancer, 12 and breast cancer. 9 CD24 plays important roles in tumorigenesis, [35][36][37] progression [38][39][40] and drug resistance. 18,41 CD24 is considered to be a negative cancer stem cell marker, specifically in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…KLF4 was reported to be downregulated in UC and act as a metastasis suppressor inhibiting EMT [85] . Androgen receptor (AR) was reported to promote UC metastasis by affecting CD24 [86] , [87] , [88] . Several investigators reported that infiltrating neutrophils [89] and B lymphocytes [90] modulated AR transactivation leading to elevated MMPs expression and cell invasion.…”
Section: Metastasis Promoters and Suppressors Of Ucmentioning
confidence: 99%
“…Further, other studies suggested GON4L drives proliferation by human cancer cells (3840). Given these findings, we explored the possibility that GON4L deficiency due to the Justy mutation affects the expression of genes that control cell-cycle progression and division.…”
Section: Resultsmentioning
confidence: 92%
“…For example, GON4L deficiency in zebrafish embryos blocks erythropoiesis, somite formation, and tail extension, which was correlated with cell cycle arrest and apoptosis (34, 37). Validating a role in cell division, other studies identified GON4L as important for the growth of cultured human cancer cells (3840). …”
Section: Introductionmentioning
confidence: 99%